(untitled) - Meer, Cornelius van der (London, 1990)
The book analyses how various political and economic factors have interacted to prevent Japan achieving high agricultural productivity at the same time as it was experiencing remarkable growth in its industrial productivity. Solutions to the current problem are suggested and the book concludes by discussing the relevance of Japan's experience to other developing economies.
Keywords: Agricultural productivity,Agriculture and state,Năng suất nông nghiệp,Nhà nước và nông nghiệp; Japan,Japan,Nhật Bản,Nhật Bản